Chicana art : the politics of spiritual and aesthetic altarities - Pérez, Laura Elisa (Objects/histories., 2007)
In Alma Lopez's digital print Lupe & Sirena in Love (1999), two icons-the Virgin of Guadalupe and the mermaid Sirena, who often appears on Mexican lottery cards-embrace one another, symbolically claiming a place for same-sex desire within Mexican and Chicano/a religious and popular cultures. Ester Hernandez's 1976 etching Libertad/Liberty depicts a female artist chiseling away at the Statue of Liberty, freeing from within it a regal Mayan woman and, in the process, creating a culturally composite Lady Liberty descended from indigenous and mixed bloodlines. In her painting <I.